Water heaters low-voltage electrode with current supply complex shape - E. V. Ptitsyna; D. V. Ptitsyn; A. B. Kuvaldin (Омский научный вестник)
At present, it remains urgent to develop effective electrode water heaters related to the need for more sophisticated technical means of electric heating of water for individual processes within enterprises. In the article on the example of the physical model of the low-voltage electrode of the heater there is described in the experimental study of the influence of the electric mode with the current supply of complex shape in the process of heating water. The aim of the work is to study the heating processes in electrode water heaters when changing the electrical modes (amplitude and frequency of the supply voltage (current)) to select the effective operating modes of the units. This required the solution of scientific problems in the development of research methods on the physical model of the water heater, obtaining regulatory characteristics that develops recommendations for the selection of effective operating modes required for the subsequent development of the algorithm of automatic control system. The solution of the tasks establishes the influence of the electromagnetic component, along with the temperature component, on the water heating processes: it is experimentally proved that at the same temperature rise speed, the value of the power factor of the plant increases from 0.67 to 0.975. The mode with a power supply of a complex shape causes an increase in the efficiency of the electrode water heaters.